Darija and the global multilingual digital landscape - Lafkioui, Mena B. (Lingua Posnaniensis, 2026)
The present study investigates how Darija, within a complex multilingual and digital context, is reshaping the roles of traditionally dominant languages like Standard Arabic and French. It highlights a shift towards a more symmetrical sociolinguistic system, where local interactions redefine linguistic functions. The research also explores how Darija interacts with the Tamazight languages in the global digital sphere, addressing conflicts and competitions. It delves further into the concept of ‘Darijation’, an unintended result of North African language policies, and reveals that Darija is increasingly displacing other languages, creating a new linguistic landscape.